The use of Pseudomonas spp. as bacterial biocontrol agents to control plant diseases - Hӧfte, Monica (Burleigh Dodds Series in Agricultural Science, 2021)
Most Pseudomonas biocontrol strains are associated with the rhizosphere of plants, where they control soil pathogens by antibiosis or competition, and leaf pathogens via induced systemic resistance. Genome mining and the division of the vastly heterogeneous genus Pseudomonas in phylogenomic (sub)groups has clarified the relation between biocontrol characteristics and phylogeny. Based on their activity, Pseudomonas biocontrol strains come in three types. A first type, represented by P. chlororaphis, P. protegens, P. corrugata and P. aeruginosa (sub)group strains, produces an arsenal of secondary metabolites with broad antimicrobial activity. The second type is found in the P. putida, P. fluorescens, P. koreensis, P. mandelii, and P. gessardii (sub)group. The spectrum of biocontrol properties of these strains is less diverse and involves siderophores and cyclic lipopeptides. The third type colonizes above-ground plant parts. Strains from this type mainly belong to the P. syringae group and are used to control postharvest pathogens. This chapter starts with recent advances in Pseudomonas taxonomy and a summary of its most important biocontrol traits. It then provides an overview of the most important Pseudomonas groups and subgroups harboring biocontrol strains. Examples of well-characterized and representative biocontrol strains show the links between phylogeny, ecology and biocontrol traits. The chapter concludes by reviewing commercially-available biocontrol strains.